Effects of beer, wine, and baijiu consumption on non-alcoholic fatty liver disease: Potential implications of the flavor compounds in the alcoholic beverages - Zhou, Yabin; Hua, Jin; Huang, Zhiguo (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease and its global incidence is estimated to be 24%. Beer, wine, and Chinese baijiu have been consumed worldwide including the NAFLD population. A better understanding of the effects of these alcoholic beverages on NAFLD would potentially improve NAFLD patient management, reduce the risks for progression to fibrosis, cirrhosis, and hepatocellular carcinoma. There is evidence suggesting some positive effects, such as antioxidative effects of bioactive flavor compounds in beer, wine, and baijiu. These effects could potentially counteract the oxidative stress caused by metabolism of ethanol contained by the beverages. In the current review, we aim to evaluate and discuss the current human and laboratory-based studies evidence of effects on hepatic lipid metabolism and NAFLD from ingested ethanol, the polyphenols from beer and wine and the bioactive flavor compounds in baijiu and the potential mechanism. It is concluded that for potential beneficial effects of wine and beer on NAFLD, inconsistence and contrasting data exists suggesting the need for further studies. There is insufficient baijiu specific human-based study for the effects on NAFLD. Although laboratory-based studies on baijiu showed antioxidative effects of the bioactive flavor compounds on the liver, it remains elusive whether the antioxidative effect from the relative low abundance of the bioactivate compounds could outweigh the oxidative stress and toxic effects from the ethanol component of the beverages.